"Be careful!" Perceptions of work‐safety culture among hired Latinx child farmworkers in North Carolina. Issue 12 (4th September 2019) - Arcury, Thomas A.; Arnold, Taylor J.; Mora, Dana C.; Sandberg, Joanne C.; Daniel, Stephanie S.; Wiggins, Melinda F.; Quandt, Sara A.
Abstract : Background: Children as young as 10 years of age can be hired to work on farms. Many of these hired child farmworkers are Latinx. Although these children experience high rates of injury, little research has addressed work‐safety perceptions among hired Latinx child farmworkers. Methods: For this qualitative study, we conducted in‐depth interviews in North Carolina in 2016 with 30 Latinx child farmworkers, ages 10 to 17. Our analysis used the work‐safety culture conceptual framework to delineate their perceptions of the psychological, behavioral, and situational elements of safety culture. Results: The child farmworkers describe a weak work‐safety culture. Psychologically, they understand that their parents want them to be safe, but they observe that safety is important to only a fraction of their supervisors and coworkers. Behaviorally, they recognize many of the hazards they confront while working, but it is not clear how well they use this knowledge to mitigate these hazards or to change their behaviors to avoid these hazards. Situationally, several children note that the only safety training they receive is the imperative to "be careful." Most receive little formal training, much of the training they receive is informally provided by family members and coworkers rather than supervisors, and their training is geared more toward how to complete a task than how to complete the task safely. Conclusions: Child farmworkers perceive that work‐safety culture is of limited importance in agriculture. Regulations are needed that improve work‐safety culture in agriculture, especially for those vulnerable due to minority age.